Risk factors associated with the prevalence of Helicobacter pylori among community members in Kibwezi West Sub-County, Makueni County - Muma, Benedict M.; Osero, Justus O.; Kanini, Caroline M. (International Journal Of Community Medicine And Public Health, 2022)
Background: Helicobacter pylori are gram-negative pathogens that live in the digestive tract and are linked to intestinal ulcers, stomach ulcers, chronic gastritis, stomach cancer, and a variety of extra-gastric problems. Close to half of the world’s populace is afflicted. The principal focus of the investigation sought to establish the extent of H. pylori infection in Kibwezi West Sub-County and the socioeconomic parameters that drive it. Methods: Purposeful selection, cluster selection, and simple random sampling strategies were utilized in the study’s analytic cross-sectional architecture. Participants ranged from 18 to 70 years old, and their stool samples (344) were analyzed using the concept of immunochromatography in vitro to determine the antigens of H. pylori in stool. At p≤0.05, Chi2 tests were conducted between independent and dependent variables. Results: A number of 344 residents of Kibwezi West Sub-County were surveyed, with a response rate of 100% (344). The majority of those sampled were aged below 58 years (90.1%, n=310), married (81%, n=280), female (75%, n=259), and practicing Christians (84%, n=288). The H. pylori test results indicated 32% (n=109) tested positive, with 68% (n=225) returning negative results. The statistical significance of education level (p=0.024), source of drinking water (p=0.001), and diabetic status (p=0.010) was confirmed. Conclusions: The prevalence of H. pylori is lower that reported in most Kenyan studies, including the Kenya health information system for Kibwezi West Sub County in the year 2020. Infection with H. pylori was strongly linked to education, drinking water source, and diabetes. This study proposes a number of intervention strategies.